Ecological Analysis Of Complete Basic Immunization Coverage For Infants In Indonesia (2017-2019) - Yuli Puspita Devi; Sabarinah Prasetyo; Muthmainnah Muthmainnah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: Complete basic immunization for infants in Indonesia is an obligation in an effort to protect infant health. It is one of the important indicators in determining the quality of health services in a certain area. However, the coverage of complete basic immunization in Indonesia in 2017 and 2018 has not been achieved nationally with National Strategic Planning and it has not been achieved the targets of 80% of districts/cities in 2019. Objective: This study aims to analyze the factors correlated to the complete basic immunization coverage of infants in Indonesia in 2017-2019. Methods: Ecological analysis was carried out using secondary data from the report of the Ministry of Health of the Republic of Indonesia in 2017-2019. Univariate analysis was conducted using descriptive statistics and one sample Kolmogorov Smirnov. Bivariate analysis was conducted by correlation test (Pearson and Spearman) and scatter plot. Results: Complete basic immunization for infants had a significant correlation with the adequacy of midwives at the primary health care in 2017 (r = -0.337). There was significant correlation between poverty and complete basic immunization in 2017 and 2018 (r = -0.362 and r = -0.535). In 2019, active Integrated Service Post (Posyandu) was correlated to the complete basic immunization (r = 0.444). The first neonatal visit was correlated to the complete basic immunization of infants for three consecutive years (2017-2019). Conclusion: Efforts that can be made to increase the coverage of complete basic immunization in Indonesia are increasing the distribution of midwives in Indonesia, increasing the coverage of the first neonatal visit by paying attention to Posyandu cadres, especially in provinces with high poverty rates.